(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article provides a comprehensive analysis of the economic, geographical, technological, and social aspects of the territorial development of cotton-textile clusters in the Kashkadarya region. A strategy for forming clusters has been established based on the region’s natural resources, transport infrastructure, labor potential, and industrial capacity. It also outlines ways to increase production efficiency, strengthen export potential, and diversify the regional economy by effectively integrating cotton cultivation and processing.